The Perfect Bikini Body: Can We All Really Have It? Loving Gaze as an Antioppressive Beauty Ideal. (12th April 2017) - Protasi, Sara
Abstract : In this paper, I ask whether there is a defensible philosophical view according to which everybody is beautiful. I review two purely aesthetical versions of this claim. The No Standards View claims that everybody is maximally and equally beautiful. The Multiple Standards View encourages us to widen our standards of beauty. I argue that both approaches are problematic. The former fails to be aspirational and empowering, while the latter fails to be sufficiently inclusive. I conclude by presenting a hybrid ethical–aesthetical view according to which everybody is beautiful in the sense that everybody can be perceived through a loving gaze (with the exception of evil individuals who are wholly unworthy of love). I show that this view is inclusive, aspirational and empowering, and authentically aesthetical.